Analysis of the Effect of Dynamic Pricing Based on Intelligent Transportation Systems on User Preferences for Online Transportation Modes - Azzah Ula Nabillah Yoni; Mega Sintya Ose Attawuwue; Rizal Aprianto (Generation Journal, 2025)
The development of digital technology in the transportation sector has led to the emergence of online transportation services with the application of dynamic pricing based on Intelligent Transportation Systems (ITS). This study aims to analyze the influence of perceptions toward dynamic pricing and ITS on users' preferences in choosing online transportation modes. The method used is quantitative descriptive, with a questionnaire distributed to 81 PKTJ Tegal students as the sample, selected through purposive sampling technique. Data were analyzed using descriptive statistics via SPSS to identify trends in respondents' perceptions and preferences. Results indicate that perceptions of ITS have a high average score (4.04), followed by preferences for using online transportation modes (3.97), and perceptions of dynamic pricing (3.62). These findings indicate that fares are fluctuating, and users' trust in the efficiency and fairness of the ITS system remains high for online transportation services. This study contributes to providing an empirical overview of the importance of ITS in improving service quality and user preferences, as well as offering recommendations for the broader development of ITS-based transportation systems, particularly in developing cities like Tegal